2013
DOI: 10.1002/clen.201200259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Runoff Dynamic on Sediment and Nitrogen Losses in an Agricultural Watershed of the Southern Shaanxi Region, China

Abstract: The southern Shaanxi region will become a water source area of the middle route of the South-to-North Water Diversion Project after 2014. However, there is little knowledge of water quality conditions in the region. Therefore, 12 rainfall events were monitored to investigate the effect of runoff dynamics on sediment and nitrogen (N) losses during the 2011 rainy season in the Hougou agricultural watershed. The results showed that at the seedling stage (SS), most of the rainfall contributed to an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The evaluated results (especially regressions after runoff separation), showed that the pollution coming from non‐point sources (including tile drainage systems) was relatively variable for all the monitored parameters and that the solute loads were influenced predominantly by hydrology. This is in agreement with findings from similar studies . The monthly specific solute loads for all monitored subcatchments, i.e.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The evaluated results (especially regressions after runoff separation), showed that the pollution coming from non‐point sources (including tile drainage systems) was relatively variable for all the monitored parameters and that the solute loads were influenced predominantly by hydrology. This is in agreement with findings from similar studies . The monthly specific solute loads for all monitored subcatchments, i.e.…”
Section: Resultssupporting
confidence: 93%
“…In general, all these phenomena depend on the ‘behaviour’ of various catchment segments in different phases of the year or during R–R events in relation to the natural, anthropogenic or ‘mixed’ factors . These factors are the weather course, land cover (land use and management, crop/tree, type and timing of agro‐technology/forest operation management), application of fertilizers, heterogeneous physical and chemical soil properties, geomorphological, hydrological and hydrogeological conditions of a watershed and land improvement interventions in various watershed zones .…”
Section: Introductionmentioning
confidence: 99%
“…Runoff and vegetative ground cover were the main factors that were responsible for the differences in sediment and nitrogen losses . The runoff dynamics and stage of crop were the main responsible factors for sediment and nitrogen losses from agricultural watersheds . It can also be observed that for <50% grass coverage treatment, irrespective of the discharge, erosion started.…”
Section: Resultsmentioning
confidence: 94%
“…If the return flow were to be reused, e.g. unused water in upstream area being reused in downstream area, redundant water diversion project and secondary investment would be required [15]. Considering the commodity value of irrigation water itself and economic connotation involved in management of irrigation water, we should maximize its one-time utilization rate and minimize the costs of secondary utilization [16].…”
Section: Connotation Of Irrigation Water Use Efficiencymentioning
confidence: 99%